2008
DOI: 10.1086/592757
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology and Interferon Susceptibility of the Natural Recombinant Hepatitis C Virus Strain RF1_2k/1b

Abstract: All identified RF1-type strains appear to be introduced from a single source, suggesting that intergenotypic recombination in HCV is sporadic and not associated with cocirculation of different genotypes in a population. The RF1 strain in this study was responsive to interferon in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
57
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 38 publications
3
57
0
Order By: Relevance
“…It is now generally hypothesized that the generation of HCV recombinants is the result of "strand switching" during replication, 17 and multitypic HCV infection is the prerequisite factor for recombination, 18 so we mainly investigated HCV recombinants in the repeatedly exposed IDUs and hemodialysis patients. Given that recombinant strain 2k/1b was spreading in ordinary patients, 6,11,13,16 we also investigated HCV recombinants in the other patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is now generally hypothesized that the generation of HCV recombinants is the result of "strand switching" during replication, 17 and multitypic HCV infection is the prerequisite factor for recombination, 18 so we mainly investigated HCV recombinants in the repeatedly exposed IDUs and hemodialysis patients. Given that recombinant strain 2k/1b was spreading in ordinary patients, 6,11,13,16 we also investigated HCV recombinants in the other patients.…”
Section: Discussionmentioning
confidence: 99%
“…15 The overlap in genotype distribution would theoretically increase the chance of multitypic HCV infection and, thus, the likelihood of intragenotypic and intergenotypic HCV recombination, especially in cases of repeatedly exposed intravenous drug users (IDUs) and hemodialysis patients. Given the implications of recombination for virus evolution, development of vaccines and antiviral therapies, 16 it is clearly important to systematically assess the prevalence of HCV recombinants in different parts of the world.…”
Section: Introductionmentioning
confidence: 99%
“…Literature shows discrepant results regarding pegINF treatment and SVR. Kurbanov et al (2008aKurbanov et al ( , 2008b showed higher susceptibility of the 2k/1b genotype to pegINF/RBV treatment in contrast to Morel et al (2010). Currently, a new DAA, sofosbuvir, shows pangenotypic HCV activity in chronic HCV patients with high rates of SVR when given with RBV (Koff, 2014).…”
mentioning
confidence: 95%
“…The recombinant genotype 2k/1b was first described in St Petersburg in 2002 in intravenous (IV) drug users (Kalinina et al, 2002). Since its discovery, the genotype 2k/1b has been detected in many countries, including Ireland, Uzbekistan, Cyprus, France, the Netherlands, and Russia (Demetriou et al, 2009;Kalinina et al, 2002;Karchava et al, 2015;Kurbanov et al, 2008aKurbanov et al, , 2008bMoreau et al, 2006;Morel et al, 2010;Raghwani et al, 2012). In all these cases, the patients originated from Russia or Georgia.…”
mentioning
confidence: 99%
“…A CRF is a recombinant form that is found repeatedly in different patients. Since its discovery, CRF01_1b2k has been isolated from patients in many countries, including Ireland, France, Cyprus, Azerbaijan, Uzbekistan, and Russia (20,25,26,29,(37)(38)(39). CRF01_1b2k is the only recombinant strain of HCV to have transmitted widely; therefore, it is important to investigate its genesis and dissemination in order to understand why it might be unique and to evaluate the likelihood that other HCV recombinant forms could increase in prevalence in the future.…”
mentioning
confidence: 99%